Efektivitas Mahkamah Pidana Internasional Dalam Menangani Kejahatan Terorisme Dan Implikasinya Terhadap Penegakan Hukum Internasional - Noval Dwi Satria; Dwi Putri Lestarika; Wevy Efticha Sary (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This study examines the effectiveness of the International Criminal Court (ICC) in addressing terrorism and its implications for international law enforcement. Based on the 1998 Rome Statute, the ICC has limited jurisdiction as terrorism is not explicitly categorized as an international crime. A normative legal research method with legislative and conceptual approaches was employed to analyze international legal instruments and the ICC’s role. Findings reveal that the ICC can indirectly address terrorism through crimes against humanity, but its effectiveness is hindered by the absence of a universal definition of terrorism, jurisdictional limitations, and insufficient ratification of the Rome Statute. The implications highlight the ICC’s contribution to strengthening international legal norms and fostering global cooperation, though amendments to the Rome Statute are needed to explicitly recognize terrorism as a core crime. The conclusion underscores the necessity of harmonizing terrorism definitions and legal reforms to enhance the ICC’s role in enforcing international law.